Mesh Infection and Migration after Umbilical Hernia Repair - Ripetti, Valter; Vaccara, Vincenzo L.; Angelini, Eleonora; Giorgio, Giovan B.; Alloni, Rossana (Scientific Research, 2013)
Mesh infection and migration are dangerous and common complications after hernia repair. Many factors cause mesh migration, which may or may not be associated to infection. Before performing hernia repair using a mesh, it is important to choose the right device to avoid this kind of complication, above all in the presence of contaminated wounds or fields. We describe two cases of mesh infection and migration after umbilical hernia repair which were treated, in accordance with recommendations in the literature, by removing the infected mesh and replacing it with a biological mesh. Our experience confirms the feasibility of using biological mesh to perform umbilical hernia repair after infection, with consequent migration, of the previously placed mesh. Our cases are the first to be reported in which mesh migration is associated with infection after umbilical hernia repair, and they demonstrate the advantages of biologic implants in abdominal wall reconstruction
Keywords: Umbilical; Infection; Migration Hernia; Mesh